Experimental study on pore structure alteration of deep shale under liquid nitrogen freezing based on nuclear magnetic resonance. (1st January 2023) - Qu, Hai; Hu, Yushuang; Guo, Ruichang; Lin, Congcong; Xu, Jianian; Jun, Hong; Chen, Xiangjun
Abstract: Freezing by liquid nitrogen (LN2 ) can noticeably alter the rock structure of rocks, which can find application in the extraction of clean natural gas for shale gas reservoirs. More natural gas exists in the deep shale formation. However, the pore structure alteration of deep shale treated by LN2 freezing remains unclear. To address this issue, experiments were conducted with three types of deep shales. The contents of mineral components were measured by X-ray diffractometry (XRD). The alteration of physical properties of the deep shale were analyzed by Nuclear magnetic resonance (NMR) and scanning electron microscope (SEM). The results indicated that LN2 was a promising fluid to induce bedding planes and longitudinal fractures, especially in carbonaceous shale. The generated fractures will connect pores to increase the permeability of shales. Repeated freezing cycles generated cracks at micro and macro levels and created high-conductivity fracture networks in shale. Water saturation has little effect on the porosity change of shales with low porosity. A novel model was developed for predicting the increased porosity after LN2 freezing. The crucial findings will guide the development of deep shale resources using cryogenic LN2 fracturing. Highlights: Pore structure evolution of deep shales were analyzed by nuclear magnetic resonance technology. Microscopic mornopoly was observed by scanning electron microscope. Freezing cycles had the most significant effect on shale structure deterioration. A correlation model was developed for predicting the increased porosity.